PENGARUH STANDAR NASIONAL PENDIDIKAN TERHADAP KESEMPATAN KERJA LULUSAN AKUNTANSI MELALUI KELUARAN SATUAN PENDIDIKAN SMK DI KOTA SURABAYA - Andriansyah, Eka Hendi (UNIVERSITAS NEGERI SURABAYA, 2013)
This study aims to determine the effect of the graduates job opportunities on the National Education Standard mediated by vocational schools in Surabaya. The study was conducted at 31 vocational schools in Surabaya, particulary the accounting department. The study concludes that the implementation of National Education Standard results in good education quality; however, the academic achievement is not used as a reference bythese graduates in obtaining job relevant to their expertise. It is expected that later researchers focus on softskill variables or other possible mediating relationships between the SNP and the graduates profession. Also, the further researchers need to extent the object of the study.